Pantauan Realisasi Anggaran Sebagai Pedoman Penyerapan Target Anggaran Melalui Dashboard Dinas KOMINFO - Oleh Soleh; Rosdiana Rosdiana; Oktafiani Khofifah (UNIVERSITAS RAHARJA, 2021)
Every Government is required to have a budget plan that is the basis for carrying out an activity and a Budget Realization Report (LRA) is needed which contains the results of activities that have been achieved in connection with the use of the budget. LRA can be used by report users to evaluate decisions in the allocation of economic resources and accountability to increase the benefits of managing money in government. The Department of Communication and Informatics of Tangerang City has problems in managing budget realization, namely the processing and monitoring process still uses Microsoft Excel, so it is difficult to control when there is an inspection report on the realization of the activity budget because the documents produced are still in the form of paper which allows damage or loss. The use of BSC (Balanced Scorecard) analysis which can measure the capability of a system, in view of the Business Process, this system can monitor the efficiency and effectiveness of budget realization management. PHP is used as a language and a temporary Mysql database for system design using the Unified Modeling Language (UML). This system produces a system that can monitor the realization of a web-based budget that can be useful for agencies in the process of processing and monitoring budget realization until the formation of a Budget Realization Report with an easier and faster process.